Com a fórmula de Bhaskara, resolva as seguintes equações:

a) x² - 6x + 9 = 0

b) x² - 15x + 36 = 0

c) x² - 7x + 10 = 0

2
x²+7x+10=0
a=1 b= -7 c=10

∆=b²-4ac
∆=(-7)²-4.1.10
∆=49-40
∆=9

x'= -b + √∆ : 2a
x'= -(+7) + √9 : 2.1
x'= -7 + 3 : 2
x'= -4 : 2
x'= -2

x'' = -b - √∆ : 2a
x''= -7 - 3 : 2
x''= -10 : 2
x''=-5

S={-5,-2}
Essa é a C

Respostas

2014-04-07T16:52:32-03:00
A) x² - 6x + 9 = 0 

a=1 b= -6 c= 9 

Δ = b²-4.a.c 
Δ = (-6)²-4.1.9 
Δ = 36-36 
Δ = 0 

x = -b ± √Δ / 2.a 
x = - (-6) ± √0 / 2. (1) 
x = + 6 ± 0 / 2 

x¹ = 6 + 0 / 2 
x¹ = 6 / 2 
x¹ = 3 

x² = 6 - 0 / 2 
x² = 6 / 2 
x² = 3 

S = {3}
1 4 1
A melhor resposta!
2014-04-07T16:54:47-03:00
A) x= 3

b) x=3 e x=12

c) x=2 e x=5
2 5 2